Strategi Pengelolaan Sampah di Daerah Aliran Sungai (DAS) Air Dingin Kecamatan Koto Tangah Kota PadangMenggunakan Pendekatan Community Based Development - Desi Eka Putri; Efendi Efendi; Sefrinal Sefrinal; Veni Veni; Okviani Syafti; Ramadhani Ramadhani; Hary Febrianto; Andri Yanto (Geosfera: Jurnal Penelitian Geografi, 2025)
This article discusses the waste management strategy for the Air Dingin River Basin (DAS) in Koto Tangah district, Padang City, using a Community-Based Development Approach.This research is motivated by lack of public awareness regarding environmental proctection particularly regarding waste management. This is evident in the habit of people directly disposing of waste into the river or piling it on the banks of the Air Dingin River Basin in Balai Gadang and Batang Kabung Villages, Koto Tangah District. The purpose of this study was to determine the characteristics of waste, waste management strategies, and formulate appropriate policies for waste management using a community-based development approach. The research findings indicate that residents living along the banks of the Air Dingin River Basin (DAS) in Koto Tangah District, Padang City, generally dispose of waste directly into the river without prior waste separation. The waste characteristics include garbage, street sweeping, dead animals, and household refuse.